O uso de jogos didáticos para o ensino de botânica: uma experiência no 7º ano - BRITO, Maria do Socorro Ferreira (2024)
This work aimed to investigate the result of the application of didactic games in the Botany teaching. The data for the development of the work were collected through questionnaires applied to teachers and students at the State School of Elementary Education and Medium Esmerina Bou-Habib, located in the city of Abaetetuba-Pa. After applying the questionnaires for the students, the didactic game was used as a facilitator of the process of learning. Our results allowed us to conclude that the didactic game can be a viable, thought-provoking and interesting tool, as it allows the teacher to teach the content through through play and leaving traditional teaching. Thus, games should have a space and a longer time in pedagogical practice, as we observed that students showed a greater interest in the discipline of botany.